2009
DOI: 10.1111/j.1600-0587.2009.05712.x
|View full text |Cite
|
Sign up to set email alerts
|

What shapes Eurasian lynx distribution in human dominated landscapes: selecting prey or avoiding people?

Abstract: In the multi-use landscape of southern Norway, the distribution of lynx is likely to be determined both by the abundance of their favoured prey Á the roe deer Á and the risk associated with the presence of humans because most lynx mortalities are caused by humans (recreational harvest, poaching, vehicle collisions). We described the distribution of the reproductive portion of the lynx population based on snow-track observations of females with dependent kittens collected over 10 yr (1997Á2006) in southern Norw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 42 publications
10
108
2
Order By: Relevance
“…Wiegand et al (2008) reporting that brown bears Ursus arctos selected areas with specific NDVI characteristics, or Basille et al (2009) demonstrating that the preferred habitat of the lynx Lynx lynx includes areas of high plant productivity (as indexed by NDVI). Likewise, recent work on vervet monkey Chlorocebus pygerythrus home range location suggested that these monkeys prefer areas with elevated productivity and reduced seasonality -as indexed by NDVI -with monthly NDVI values being shown to correlate with field measurements of leaf cover and food availability for vervet monkeys (Willems et al 2009).…”
Section: Ndvi: Not Just For Large Herbivoresmentioning
confidence: 99%
“…Wiegand et al (2008) reporting that brown bears Ursus arctos selected areas with specific NDVI characteristics, or Basille et al (2009) demonstrating that the preferred habitat of the lynx Lynx lynx includes areas of high plant productivity (as indexed by NDVI). Likewise, recent work on vervet monkey Chlorocebus pygerythrus home range location suggested that these monkeys prefer areas with elevated productivity and reduced seasonality -as indexed by NDVI -with monthly NDVI values being shown to correlate with field measurements of leaf cover and food availability for vervet monkeys (Willems et al 2009).…”
Section: Ndvi: Not Just For Large Herbivoresmentioning
confidence: 99%
“…On a subhome-range scale, Basille et al (2009) found that lynx preferred areas that include large proportions of forest and areas where roe deer are abundant. On a large scale, therefore, both prey density and habitat features play a role in habitat selection by lynx.…”
mentioning
confidence: 99%
“…In the empirical model, the strong explanatory power of the land-use type forest well reflects the biology of the Eurasian lynx which prefers forests of very large extends in mountainous areas (Schadt et al 2002;Basille et al 2008Basille et al , 2009. Basille et al (2009) showed that abundances of the lynx are closely related to prey density which was not available as a variable in our data set, but the nonlinear effect of the temperature variable might well indicate an optimum which beneficially affects productivity (Melis et al 2010) and therefore continuous resource availability.…”
Section: Discussionmentioning
confidence: 75%